Alpha lipoic acid with pulsed radiofrequency in treatment of chronic lumbosacral radicular pain: A prospective, randomized study. Issue 24 (18th June 2021) - Abdelrahman, Khaled A.; Ibrahim, Abdelrady S.; Osman, Ayman M.; Aly, Mohamed G.; Ali, Abdelhady S.; Farrag, Waleed S.
Abstract: Background: The effect of adding alpha lipoic acid (ALA) to pulsed radiofrequency (PRF) for treatment of lumbar-sacral pain was evaluated. Objective: to evaluate the effect of using ALA as an adjuvant therapy with PRF for treatment of chronic lumbosacral radicular pain caused by herniated disc. Methods: One hundred twenty patients with lumbo-sacral radicular pain allocated into 2 groups. Group I: treated with PRF at 42°C for 120 seconds. Group II: treated as in group I, plus oral ALA 600 mg (Thiotacid 600 mg, EVA PHARMA, Egypt) three times per day (1800 mg/day) for 3 weeks then 600 mg once daily for 2 weeks. The lumbo-sacral radicular pain evaluated using the numerical rating pain score and Oswestry Disability Index. Results: Success rate was significantly higher in group II at 3 and 6 months after intervention. The median values of the numerical rating pain score and the Oswestry Disability Index were significantly lower in group II with no significant difference in Epworth Sleepiness Scale. No major complications were reported in both groups. Conclusion: The current study supports the use of ALA with PRF on the dorsal root ganglion for treating lumbosacral radicular pain.